(untitled) (Journal of the College of Languages (JCL), 2009)
Alice Walker’s novel The Color Purple1983, whose events take place in the rural Georgia and addresses the most important issues in the early 20thcentury; like male dominant society and women submission to men, weaves a mosaic picture of male-female relationships. Black men like Alphonso, Albert and Harpo are portrayed as oppressors, cruel and they exercise power and violence over their wives and daughters. Through the negative portrayal of black male characters, Walker is accused to be a men hating writer because she ’’Views oppression as an essentially masculine activity which springs from the male’s aggressive need to dominate. In the novel, man is the premium mobile, the one by whom and through whom evil enters the world.’’1A close look at the novel shows the opposite of this vision. Male characters are the victims of their societal wrongful and oppressive values. There are certain psychological and social agents which affect those men passively turning them into bad persons who abuse the women from their same racial decent.